Application of Interactive Learning Games in Stimulating Knowledge About Object Recognition in Early Childhood - Arifin Arifin; Mohan Taufiq Mashuri; Nana Citrawati Lestari; Erwinsyah Satria; Rizki Dewantara (Educenter : Jurnal Ilmiah Pendidikan, 2023)
Teachers and parents must pay close attention to the golden age phase of early infancy since children's growth and development can occur swiftly during this time. In the early childhood learning process, it is crucial to transfer knowledge so that children can acquire information, including the introduction of objects into the child's environment. There are already a plethora of diverse, entertaining learning materials for young children. One of them is interactive learning media that emphasizes visual features to catch children's attention during the learning process. Based on the relevance of learning media in early childhood, the purpose of this research is to build interactive learning game media in order to promote comprehension and stimulate early children's ability to recognize the introduction of things. 93.3% of students like object recognition learning media and the Figures on the learning media, 80% of students can comprehend object recognition material and can answer according to choice, and 86.67 % of students stated that the terms of color, animation, audio, video, and text were feasible. So that this object identification learning material has an appealing visual design, is simple to use, and can be comprehended by pupils.